The oxydation process of Antarctic fish hemoglobins. - VITAGLIANO L.; RICCIO A.; DI PRISCO G.; SMULEVICH G.; BONOMI, GIOVANNA; MAZZARELLA, LELIO (2004)
Analysis of the molecular properties of proteins extracted from organisms living under extreme conditions often highlights peculiar features. We investigated by UV-visible spectroscopy and X-ray crystallography the oxidation process, promoted by air or ferricyanide, of five hemoglobins extracted from Antarctic fishes (Notothenioidei). Spectroscopic analysis revealed that these hemoglobins share a common oxidation pathway, which shows striking differences from the oxidation processes of hemoglobins from other vertebrates. Indeed, simple exposure of these hemoglobins to air leads to the formation of a significant amount of the low-spin hexacoordinated form, denoted hemichrome. This hemichrome form, which is detected under a variety of experimental conditions, can be reversibly transformed to either carbomonoxy or deoxygenated forms with reducing agents. Interestingly, the spectra of the fully oxidized species, obtained by treating the protein with ferricyanide, show the simultaneous presence of peaks corresponding to different hexacoordinated states, the aquomet and the hemichrome. In order to assign the heme region state of the alpha and beta chains, the air-oxidized and ferricyanide-oxidized forms of Trematomus bernacchii hemoglobin were crystallized. Crystallographic analysis revealed that these forms correspond to an alpha(aquomet)-beta(bishistidyl-hemichrome) state. This demonstrates that the alpha and beta chains of Antarctic fish hemoglobins follow very different oxidation pathways. As found for Trematomus newnesi hemoglobin in a partial hemichrome state [Riccio, A., Vitagliano, L., di Prisco, G., Zagari, A. & Mazzarella, L. (2002) Proc. Natl Acad. Sci. USA99, 9801-9806], the quaternary structures of these alpha(aquomet)-beta(bishistidyl-hemichrome) forms are intermediate between the physiological R and T hemoglobin states. Together, these structures provide information on the general features of this intermediate state.